ESTIMASI TANGKAPAN PER UNIT UPAYA BAKU DAN PROPORSI YUWANA PADA PERIKANAN TUNA DI SULAWESI TENGGARA (Estimation of Standard Catch Per Unit Effort and Juvenile Proportion of Tuna Fishery in Southeast Sulawesi) - Naslina Alimina; Budy Wiryawan; Daniel R. Monintja; Tri Wiji Nurani; Am Azbas Taurusman (Bogor Agricultural University, 2016)
ABSTRACTTuna is an important fish commodity in Southeast Sulawesi. It valued as an export and interisland trade product as well as an important component of local fish consumption for coastal community around Southeast Sulawesi Waters (PSST). Indonesian fisheries management is currently adopting the concept of ecosystem approach to fisheries management (EAFM). EAFM implementation in Indonesia has continued by indicators establishment to assess the sustainability performance of fisheries. Catch per unit effort standard (Standard CPUE) and juvenile composition were implemented as indicators to assess resource sustainability. Data limitations are one of the issues in fisheries management at this time, however, management efforts remain to be implemented by utilizing the best available data. This study aimed to derived recent ten years coverage of standard CPUE and it trends as well as juvenile proportion in tuna fishery based on statistical data and field observation. Assessment results show that Standard CPUE in 2014 was 0,31 tons per trip and tends to increase in year coverage, while juvenile composition was 48,6%. Based on these results, the tuna fishery in Southeast Sulawesi is still sustainable. However, there is a need to have further control and monitoring, especially on a fishery that caught tuna under Lm. Management measure has to be selected carefully in line with social economic aspects of tuna fishery in this area.Keywords: EAFM, juvenile proportion, Standard CPUE, tuna——-ABSTRAKTuna merupakan komoditas perikanan penting di Sulawesi Tenggara baik sebagai produk ekspor, perdagangan antar pulau maupun pemenuhan kebutuhan lokal bagi masyarakat pesisir di perairan bagian selatan Sulawesi Tenggara (PSST). Untuk mempertahankan keberlanjutan perikanan tuna di daerah ini maka perlu adanya suatu upaya pengelolaan komprehensif yaitu pengelolaan perikanan dengan pendekatan ekosistem atau Ecosystem approach to Fisheries Management (EAFM). Implementasi EAFM di Indonesia terus dikembangkan dengan tersusunnya indikator penilaian kinerja pengelolaan. Tangkapan per Unit Upaya atau Catch per Unit Effort (CPUE) dan komposisi yuwana merupakan bagian dari indikator EAFM Indonesia khususnya dalam domain sumberdaya. Penelitian ini bertujuan untuk memperoleh nilai CPUE baku dan kecenderungannya selama sepuluh tahun terakhir, dan proporsi yuwana berdasarkan data statistik perikanan yang diintegrasikan dengan data yang diperoleh melalui pengamatan, wawancara dan pengisian kuesioner dengan pemangku kepentingan terkait. Hasil penilaian menunjukkan bahwa CPUE baku tahun 2014 adalah 0,31 ton/trip dengan kecenderungan meningkat, sedangkan komposisi yuwana adalah 48,6%. Berdasarkan nilai CPUE baku dan proporsi yuwana, maka kinerja perikanan tuna Sulawesi Tenggara masih dinilai baik. Perlu adanya upaya pengendalian dan pemantauan lebih lanjut terutama pada perikanan yang menangkap yuwana tuna. Namun demikian, pemilihan tindakan pengelolaan harus dilakukan secara hati-hati dengan memperhatikan pemenuhan kebutuhan sosial ekonomi lainnya dari perikanan tuna di daerah ini.Kata kunci: EAFM, proporsi yuwana, CPUE baku, tuna